Я - вор в законе: [роман] / Евгений Сухов - Сухов Евгений Евгеньевич (АСТ-ПРЕСС, 1997)
Экземпляры: ф.22 (2004) / Инвентарный номер: 44694 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 91 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44